Ground-, satellite- and simulation-based analysis of a strong dust event over Abastumani, Georgia, during May 2009 - Kokkalis, Panayotis; Papayannis, Alexandros D.; Mamouri, Rodanthi-Elisavet (My University, 2012)
A strong dust event over Abastumani, Georgia, during May 2009 was studied using light detection and ranging (lidar), satellite and sun photometric measurements. High aerosol optical depth (AOD) values (0.45-0.57) at 500 nm were measured over the closest Aerosol Robotic Network (AERONET) site (Erdemli, Turkey), whereas over Georgia, the AOD measured by the Moderate Resolution Imaging Spectroradiometer (MODIS) was about 0.9 at 550 nm. The AERONET data analysis showed a mean aerosol effective radius of about 2.5 μm, whereas the mean value of the Ångström exponent (α) (wavelength pair 440/870 nm) was smaller than 1, indicating the dominance of large aerosols. The aerosol lidar over Abastumani showed the existence of a strong particle load from the near ground up to a height of 3.5 km. The BSC-DREAM8b forecast model showed that the dust aerosols travelled from the Saharan and the Arabic deserts to the studied area, even reaching southern Russia, covering a total distance of about 5500 km, in the height region from about 2 to 11.5 km.
Keywords: Atmospheric aerosols; Optical radar; Radiometers